Morpho-Orthographic Complexity in Affix Spelling in Hebrew: A Novel Psycholinguistic Outlook Across the School Years - Schiff, Rachel; Rosenstock, Shlomit; Ravid, Dorit (Frontiers in Psychology, 2020)
The current study examined the factors underlying native Hebrew speakers’ ability to learn homophonous affix spelling. It takes a novel view in investigating the effect of morpho-orthographic complexity of affix representation on the development of affix spelling across the school years. The role of five morpho-orthographic principles in homophonous affix letter spelling was studied: (i) morpho-orthographic transparency; (ii) affix letter prevalence; (iii) morpho-phonological competition; (iv) overtness of the phonological-orthographic link; and (v) phono-morpho-orthographic consistency. Taken together, these five principles of affix spelling constitute complexity metrics that pinpoint the loci of spelling challenge in homophonous Hebrew affixes. Study participants were 83 monolingual Hebrew-speaking students in four grade levels – 2nd, 4th, 7th and 10th grades. The research instrument was a spelling task of 244 words containing affix letters in 57 morphological categories. The affixes appearing in the target words represented 56 different affix categories, covering all non-root morphological roles, both inflectional and derivational. While correct spelling increased across grade levels, a hierarchy emerged in interaction with grade level regarding these criteria: Younger spellers were mostly assisted by morpho-orthographic sites, morphological category frequency, and phonological transparency – while spelling in higher grade levels was more affected by morpho-orthographic prevalence. Thus, knowledge of how morphological roles are deployed in the orthography emerges as the most significant factor that affects learning to spell affix letters in Hebrew.